Micromachined Thermal Time-of-Flight Flow Sensors and Their Applications - Liji Huang (Micromachines, 2022)
Micromachined thermal flow sensors on the market are primarily manufactured with the calorimetric sensing principle. The success has been in limited industries such as automotive, medical, and gas process control. Applications in some emerging and abrupt applications are hindered due to technical challenges. This paper reviews the current progress with micromachined devices based on the less popular thermal time-of-flight sensing technology: its theory, design of the micromachining process, control schemes, and applications. Thermal time-of-flight sensing could effectively solve some key technical hurdles that the calorimetric sensing approach has. It also offers fluidic property-independent data acquisition, multiparameter measurement, and the possibility for self-calibration. This technology may have a significant perspective on future development.